Chemical substitution – oriented design of a new polar PbFIO3 achieving a balance between large second-harmonic generation response and wide band gap. (1st February 2022) - Xu, Yiyi; Lin, Chensheng; Zhao, Dan; Li, Bingxuan; Cao, Liling; Ye, Ning; Luo, Min
Abstract: A new polar iodate fluoride, PbFIO3, was designed via multisite substitution by taking BiO(IO3 ) as a prototype. It crystalizes in the polar space group Iba 2. Similar to BiO(IO3 ), it has an Aurivillius-type cationic [PbF] + layer. As regarding IO3 polyhedron in PbFIO3, they inherit the beneficial arrangement of IO3 polyhedron in BiO(IO3 ), which result in the strong second-harmonic generation (SHG) response about 8 times that of KH2 PO4 (KDP). In addition, benefiting from the introduction of strong electronegative F atoms replacing the O atoms of 2D (Bi2 O2 ) 2+ layer, PbFIO3 exhibits a larger band gap about 3.87 eV compared to BiO(IO3 ) (3.3 eV). Besides strong SHG response and wide band gap, PbFIO3 possess a moderate birefringence of 0.06@546.1 nm as well. These superior linear and nonlinear optical (NLO) properties make PbFIO3 being a potential NLO crystal. Graphical abstract: Image, graphical abstract